(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
Data about floristic records of Ionoxalis tetraphylla (Cav.) J. Rose (Oxalis tetraphylla Cav.) (Oxalidaceae), a new alien species of Ukrainian flora were presented. Species has Central American origin, its primary area are covers Mexico, Panama, Guatemala, Costa Rica, Caribbean islands. Secondary area spreads on Europe, Asia and Australia. It was found in neighboring countries with Ukraine, including Russia and Belorussia. As a naturalized species it was tagged in some countries of Southern Europe. The main centers of species introduction in Ukraine are M.M. Hryshko National Botanical Garden of NAS of Ukraine, Acad. O.V. Fomin Botanical Garden of Taras Shevchenko Kyiv National University, Botanical Garden of Oles’ Honchar Dnipro National University, Botanical Garden of V.N. Karazin Kharkiv National University, Botanical Garden of V.I. Vernadsky Taurian National University, Syretskyi dendrological park (Kyiv), private gardens and greenery managements in Kyiv and Kyiv Region, Odesa, Kamyanets-Podilskyi (Khmelnytskyi Region) and other regions of the country. Information about spontaneously distribution of the plants in Ukraine nowdays is absent. At the first time some escaped plants of the I. tetraphylla were recorded in 2019 near village Dovzhyk of Zhymomyr District of Zhytomyr Region. Some individuals grew in old pine forest margins near path. Plants successfully overwintered at 2019/2020 years. Taxonomical and morphological characteristics, chorological data (primary and secondary areas) and ecological peculiarities are presented. According to the time of immigration this species is kenophyte, according to the way of introduction – ergasiophyte and according to the degree of naturalization in Ukraine it is ephemerophyte. The species is mesotroph, mesophyte, scio-heliophyte. In conditions of Ukraine it blooms profusely but almost never forms seeds, and reproduces vegetatively – by daughter bulbs. The map of the species distribution (spontaneously and in culture) in Ukraine is presented.